WACANA “HIKMAH” DALAM SURAT KABAR HARIAN REPUBLIKA - Mohammad Fakhrudin (p-ISSN 2356-0576, 2014)
ABSTRACT: This research aims at describing (1) the structure of “Hikmah” discourse and (2) the themes discussed and the way of discussing ones. Qualitative and descriptive approaches are utilized in this research. The techniques of collecting data used here are observation  and literature review. The data are noted on data noting-form. The research instrument used to provide the data is the researcher himself, equiped by the data-noting form. Then, the forms are saved in the hard disk. Next, the data are analyzed using content-analysis technique. The results of data-analysis are discussed using informal technique. Based on the data and the discussion, it is concluded that (1) the structure of “Hikmah” discourse generally consist of title, introduction, content, and closing. Most of the titles in the articles function to inform clearly the topik being disscussed. The introduction contains some interesting stories, such as the story of Nabi, sahabat,  or common people who hase peculiarity; the quotes from the meaning of Alquran or Hadis; opinion of ulama, and experts, or the explanation of important problem being disscussed in the article. Furthermore, the content part of the article contains the discussion of problem. Generally, the quotes taken from several verses of Alquran or Hadis, opinion and/or action of well-kown ulama and/or expert, or writers themselves. The closing part commonly contains the message or the hope of the writers. Then, the next conclusion is that the themes are various. The ways the writers discussed the themes are also comprehensive. Keywords: discourse structure, discourse theme, “Hikmah” discourse ABSTRAK: Penelitian ini bertujuan mendeskripsikan (1) struktur wacana “Hikmah” dan (2) tema yang dibahas dan cara membahasnya. Dalam penelitian ini digunakan pendekatan kualitatif dan deskriptif. Pengumpulan data dalam penelitian ini dengan teknik observasi dan studi pustaka. Data itu dicatat dalam form pencatat data. Instrumen yang digunakan dalam penelitian ini adalah peneliti sendiri dilengkapi dengan form pencatat data. Form pencatat data disimpan dalam hard disk. Analisis data dilakukan dengan teknik analisis isi. Hasil analisis selanjutnya disajikan dengan teknik informal. Berdasarkan data dan pembahasannya, penelitian ini disimpulkan (1) struktur wacana rubrik “Hikmah” umumnya terdiri atas judul, bagian pendahuluan, bagian inti, dan bagian penutup. Sebagian besar judul tulisan pada rubrik itu berfungsi memberikan informasi secara jelas mengenai masalah yang dibahas. Bagian pendahuluan berisi kisah menarik, baik kisah Nabi, sahabat, maupun orang biasa yang mempunyai keluarbiasaan; kutipan makna ayat Alquran atau Hadis; pendapat ulama, pendapat pakar, atau paparan masalah penting yang akan dibahas. Bagian inti wacana berisi pembahasan masalah. Pada bagian ini disajikan kutipan ayat dan/atau Hadis, pendapat dan/atau tindakan ulama masyhur dan/atau pakar atau pendapat penulis sendiri. Bagian penutup umumnya berisi pesan atau harapan penulis. (2) Tema-tema yang dibahas sangat variatif. Cara penulis membahas tema itu sangat komprehensif. Kata kunci: struktur wacana, tema wacana, wacana “Hikmah”